2004
DOI: 10.1515/jpem.2004.17.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Orlistat as an Adjunct to Behavioral Treatment in Overweight African American and Caucasian Adolescents with Obesity-related Co-morbid Conditions

Abstract: This pilot study compared the efficacy of orlistat as an adjunctive treatment for obesity between African American and Caucasian adolescents. 20 obese adolescents with obesity-related comorbid conditions underwent measurements of body composition, glucose homeostasis by frequently sampled intravenous glucose tolerance test (FSIGT), and fasting lipids before and after 6-months' treatment with orlistat 120mg TID in conjunction with a comprehensive behavioral program.Weight (p< 0.05), BMI (p<0.001), total cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 73 publications
2
48
0
5
Order By: Relevance
“…In another uncontrolled study, a 4 kg weight loss was reported in 11 prepubertal children within 3 months [8]. A follow-up of former study was recently published demonstrating similar results at 6 months of treatment [7]. There are no medium-term studies published in paediatric population regarding efficacy and tolerability of orlistat.…”
Section: Discussionmentioning
confidence: 99%
“…In another uncontrolled study, a 4 kg weight loss was reported in 11 prepubertal children within 3 months [8]. A follow-up of former study was recently published demonstrating similar results at 6 months of treatment [7]. There are no medium-term studies published in paediatric population regarding efficacy and tolerability of orlistat.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to have modest weight loss efficacy in obese children and adolescents. [183][184][185][186][187] The largest study (n=539) of orlistat in obese adolescents reported a placebo-subtracted reduction in BMI of 0.86 kg/m 2 (BMI reduction of ≈2.4%) over a treatment period of 1 year. 183 No cardiometabolic benefits were observed other than a small reduction in diastolic blood pressure.…”
Section: Orlistatmentioning
confidence: 99%
“…На фоне лечения подростки снизили вес в среднем на 8,7±1,2%, жен-щины -на 13,6±4,2% от исходных значений. В обеих группах шло улучшение антропометрических показа-телей и нормализация липидного спектра крови, на что также указывают большинство исследователей, приме-нявших орлистат, как у взрослых [6,14,20], так и у под-ростков [12,16,18].…”
Section: результаты исследования и их обсуждениеunclassified
“…Пять подростков отказались от лечения на I этапе из-за развившихся у них побочных эффек-тов. Такую же реакцию у подростков наблюдали прак-тически все исследователи, применявшие орлистат для лечения ожирения в этой возрастной группе [12,16,18], что объясняется сниженной мотивацией к про-водимому лечению и отсутствием у детей подростко-вого возраста полного представления о ценности своего здоровья [5].…”
Section: результаты исследования и их обсуждениеunclassified